Transformation of the economic role of local self-government in low-urbanized territories in Ukraine: Initial conditions and social perception - Nazar Hlynskyy; Yevhen Krykavskyy; Olha Hirna; Yuliia Savchenko (International Journal of Management and Economics, 2022)
Newly formed territorial communities acquire a real subjectivity in the processes of the management of territorial development: they become responsible for a significant share of day-to-day economic activities within their sphere of responsibility, especially in territories with a predominantly rural population. This article aimed to study the changing role of local self-government in ensuring the economic development of the low-urbanized territory, determining public opinion and expectations of residents from local governments in the new conditions. A public opinion poll of residents living in selected local communities was conducted. This article identified the objective factors of the level and pace of newly formed territorial communities' development in Ukraine. It has been proved that the decentralization of power changes the role of local government and the expectations of residents from it and their assessments of the situation at the local level.
Keywords: H83; O18; R11; 650; decentralization of power; local economic development; local self-government; low-urbanized territories; social perception